Correlação entre a infecção por SARS-CoV-2 e sintomas de depressão, ansiedade e estresse: uma revisão narrativa - Demichelli, Shayene Berti (My University, 2025)
Introduction: The COVID-19 pandemic reached high proportions, mainly affecting the physical and mental health of the population. The lack of knowledge about the virus that causes the disease, SARS-CoV-2, has resulted in a large number of infected people who have severe symptoms, including neuropsychological disorders, which persisted after the end of treatment. This narrative review aimed to gather studies and discuss the scenarios impact of the infection on the central nervous system, as well as the severity of symptoms of depression, anxiety and/or stress. Methods: The search was performed in the PubMed/Medline database in December 2022. The following were used: inclusion criteria: (1) original articles published between June 2020 and December 2022; (2) in English language; (3) which include patients infected with SARS-CoV-2; (4) that has the measure of depression severity as an outcome, anxiety and/or stress assessed by validated scales. Results: The database search found 649 articles. After screening, 325 articles were excluded for not being original articles, leaving 305 articles. Articles that did not deal with SARS-CoV 2 infection were excluded, leaving 29 articles. After reading the complete analysis of the studies, 6 articles were selected and included in the discussion this narrative review. Conclusion: Studies show that mental health disturbances associated with SARS-CoV-2 infection may persist after the treatment and cure of the disease, and may get worse if they are not identified and treated correctly. Despite the relevance of the studies analyzed, the literature still lacks research evaluating the relationship and severity of these symptoms with SARS-CoV-2 virus infection. [resumo fornecido pelo autor]
Introdução: A pandemia da COVID-19 atingiu proporções elevadas, afetando principalmente a saúde física e mental da população. A falta de conhecimento sobre o vírus causador da doença, SARS-CoV-2, acarretou em uma grande quantidade de pessoas infectadas que apresentaram sintomas graves, incluindo transtornos neuropsicológicos, que persistiram após o término do tratamento. Esta revisão narrativa teve como objetivo reunir estudos e discutir os cenários do impacto da infecção no sistema nervoso central, bem como a gravidade dos sintomas de depressão, ansiedade e/ou estresse. Métodos: A busca foi realizada na base de dados PubMed/Medline em dezembro de 2022. Foram utilizados os seguintes critérios de inclusão: (1) artigos originais publicados entre junho de 2020 e dezembro de 2022; (2) em língua inglesa; (3) que incluem pacientes infectados pelo SARS-CoV-2; (4) que tenha como desfecho a medida de gravidade de depressão, ansiedade e/ou estresse avaliados por escalas validadas. Resultados: A pesquisa na base de dados encontrou 649 artigos. Após triagem, foram excluídos 325 artigos por não serem artigos originais, restando 305 artigos. Foram excluídos artigos que não se tratavam da infecção por SARS-CoV 2, estando 29 artigos. Após leitura análise completa dos estudos, foram selecionados e incluídos 6 artigos na discussão dessa revisão narrativa. Conclusão: Estudos mostram que os distúrbios na saúde mental associados à infecção por SARS-CoV-2 podem persistir após o tratamento e a cura da doença, podendo se agravar caso não sejam identificados e tratados corretamente. Apesar da relevância dos estudos analisados, a literatura ainda carece de pesquisas avaliando a relação e a gravidade destes sintomas com a infecção pelo vírus SARS-CoV-2. [resumo fornecido pelo autor]
Keywords: SARS-CoV-2; Depressão; Ansiedade; COVID-19; Saúde mental